Revision of the European species of the subgenus Neocheilosia Barkalov (Diptera, Syrphidae: Cheilosia) - Bot, Sander; Ståhls, Gunilla; Bygebjerg, Rune; Doczkal, Dieter; Vujic, Ante (European Journal of Taxonomy, 2025)
The European species of the Cheilosia subgen. Neocheilosia Barkalov, 1983 (Diptera, Syrphidae) are revised. The identities of Cheilosia morio (Zetterstedt, 1838) and of its synonyms are reviewed, and C. scanica Ringdahl, 1937 is established as a junior synonym of C. morio. Cheilosia luteicornis (Zetterstedt, 1838) is re-installed as the name for C. morio of authors pro parte, not Zetterstedt. Cheilosia morio and C. luteicornis are redescribed, and lectotypes are designated for Eristalis lineata Wahlberg, 1843 and for E. luteicornis Zetterstedt, 1838 in order to ensure the consistent future interpretation of the names. The hitherto unknown male of Cheilosia barovskii Stackelberg, 1930 is described, and the female of C. barovskii is redescribed. We also provide updated distributional records and an identification key. Finally, we present a Neighbor-Joining tree for mtDNA COI barcodes of four species of the subgen. Neocheilosia.
Keywords: Cheilosia, COI barcodes, new synonyms, revision, species key.